Semiclassical Trajectory Studies of Reactive and Nonreactive Scattering of OH(A2Σ+) by H2 Based on an Improved Full‐Dimensional Ab Initio Diabatic Potential Energy Matrix. Issue 8 (14th March 2022) - Han, Shanyu; de Oliveira‐Filho, Antonio G. S.; Shu, Yinan; Truhlar, Donald G.; Guo, Hua
Abstract: We present a new full‐dimensional diabatic potential energy matrix (DPEM) for electronically nonadiabatic collisions of OH( A 2 Σ + ) with H2, and we calculate the probabilities of electronically adiabatic inelastic collisions, nonreactive quenching, and reactive quenching to form H2 O+H. The DPEM was fitted using a many‐body expansion with permutationally invariant polynomials in bond‐order functions to represent the many‐body part. The dynamics calculations were carried out with the fewest‐switches with time uncertainty and stochastic decoherence (FSTU/SD) semiclassical trajectory method. We present results both for head‐on collisions (impact parameter b equal to zero) and for a full range of impact parameters. The results are compared to experiment and to earlier FSTU/SD and quantum dynamics calculations with a previously published DPEM. The various theoretical results all agree that nonreactive quenching dominates reactive quenching, but there are quantitative differences between the two DPEMs and between the b =0 results and the all‐ b results, especially for the probability of reactive quenching. Abstract : Semiclassical trajectory calculations for the nonadiabatic quenching of OH(A) by H2 on a modified ab initio diabatic potential energy matrix report branching fraction of the adiabatic and nonadiabatic channels and the product internal state distribution in the nonadiabatic quenching channel. The results are in reasonable agreement with experimental and previous quantum calculations.